Analysing bioenergy and land use competition in a coupled modelling system: The role of bioenergy in renewable energy policy in Germany - Ruth Delzeit; Horst Gömann; Karin Holm-Müller; Peter Kreins; Bettina Kretschmer; Julia Münch; Sonja Peterson (Kiel Institute for the World Economy (IfW), 2010)
In the context of energy security and climate protection, biomass is given high importance. Nevertheless, land-use conflicts resulting from the cultivation of biomass and their economy-wide effects are yet to be fully understood. To shed light on this issue we link three distinctive models; a global, multi-regional general equilibrium model (DART), a regionalised agricultural sector model for Germany (RAUMIS) and a location model for biogas plants. The DART model allows capturing international and national feedback effects of an increased use of bioenergy such as increased agricultural prices. The interaction of DART and RAUMIS links global markets and connects them to the detailed specification of agricultural land use in Germany. Finally, we link this system to the newly developed location model ReSI-M that accounts for the location choices of biogas plants in Germany and the resulting regional markets for energy crop demand. As a first application of the modelling system we analyse the effects of the German Renewable Energy Source Act on German biogas production and of the EU 10%-biofuel target on German agriculture and world agricultural prices. A main result of the simulations is that accounting for existing land-use restrictions and land-use competition has a significant effect on model results.
Keywords: C61; C68; Q15; Q42; Q48; 330; bioenergy; land use; renewable energy policy; coupled models; agricultural-sector models; CGE; Förderung regenerativer Energien; Biokraftstoff; Bioenergie; Wirkungsanalyse; Landwirtschaftliche Bodennutzung; Agrarpreis; Allgemeines Gleichgewicht; Mehr-Länder-Modell; Agrargeographie; Standort; Deutschland; Welt